2022
DOI: 10.3390/s22041410
|View full text |Cite
|
Sign up to set email alerts
|

A Bearing Fault Diagnosis Method Based on Wavelet Packet Transform and Convolutional Neural Network Optimized by Simulated Annealing Algorithm

Abstract: Bearings are widely used in various electrical and mechanical equipment. As their core components, failures often have serious consequences. At present, most parameter adjustment methods are still manual adjustments of parameters. This adjustment method is easily affected by prior knowledge, easily falls into the local optimal solution, cannot obtain the global optimal solution, and requires a lot of resources. Therefore, this paper proposes a new method for bearing fault diagnosis based on wavelet packet tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…The fault diagnosis method needs to process different fault signals of dry reactor in order to obtain an evaluation criterion. Finally, the state of the dry reactor corresponding to the signal can be obtained by judging the characteristics of a certain field signal and the difference between it and the threshold value in the evaluation criterion [11]. There are many fault diagnosis methods, which method is suitable for the application of dry reactor and can obtain accurate criteria which will be the content of research.…”
Section: Multistate Fault Diagnosis Methods For Dry Reactormentioning
confidence: 99%
“…The fault diagnosis method needs to process different fault signals of dry reactor in order to obtain an evaluation criterion. Finally, the state of the dry reactor corresponding to the signal can be obtained by judging the characteristics of a certain field signal and the difference between it and the threshold value in the evaluation criterion [11]. There are many fault diagnosis methods, which method is suitable for the application of dry reactor and can obtain accurate criteria which will be the content of research.…”
Section: Multistate Fault Diagnosis Methods For Dry Reactormentioning
confidence: 99%
“…In the design of the research model, this paper takes two steps: the first step is to use the logistic model for regression fitting analysis; the second step is to conduct an intermediary test with KHB. Similar methods are often used in computational sociology ( 12 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Li [9] proposed an attention mechanism (AM) algorithm weighted long short-term memory (LSTM) neural network for the purpose of getting better fault diagnosis results in Tennessee Eastman process. He et al [10] suggested a fault diagnosis method based on wavelet packet transform and convolutional neural network. Nauyen et al [11] proposed a new DNN-based vibration signal-based bearing fault diagnosis method.…”
Section: Introductionmentioning
confidence: 99%